The External Conflict Management in Dolittle Movie - Dewa Gede Widiya Putra (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2022)
The analysis of external conflict in this study used a movie as the subject, namely Dolittle. This study aims to know the kind of conflict by the source of the conflict faced by the main character in the Dolittle movie. The qualitative method was used to collect and analyze the data, which was achieved through observation. This study aims at (1) classifying the types of external conflict, (2) describing the source of the conflict, (3) analyzing the conflict based on the conflict management strategy. The data were collected by conducting close observation of the movie. After analyzing the data, this study found that the main character faced two types of external conflict, namely, man against man and man against nature which the conflict arose dominantly caused by Limited resources. As for the conflict management strategy, the Avoidance strategy is commonly found in the main character resolving the conflict. The conclusion developed by the interpretation of the data is that it is from the kind of external conflict which is related to the source and the conflict management strategy that show the dominant data used by the main character encountered the conflict.